2018
DOI: 10.1016/j.jlumin.2017.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of valoneoyl groups on the interactions between Euphorbia tannins and human serum albumin

Abstract: Tannins belonging to plant polyphenols, are large group of compounds with diverse biological activity. Many of them are being studied as potential natural medicine due to their antioxidant, antiviral, antibacterial or anticancer properties. However, so far little is known about the structural and functional relations in protein-tannin interactions, in particularly the role of valoneoyl groups in tannin structure. In this study we first investigated the mechanisms of interaction 1,2-di-O-galloyl-4,6-valoneoyl-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…The smallest antihemolytic effect was exhibited by tannins containing a valoneoyl group (T3, T4) that is a limitation factor of the rotational mobility of the aromatic rings 46 . In addition, these tannins have a carboxyl Figure 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The smallest antihemolytic effect was exhibited by tannins containing a valoneoyl group (T3, T4) that is a limitation factor of the rotational mobility of the aromatic rings 46 . In addition, these tannins have a carboxyl Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of tannins depends on their structure and is determined not only by molecular mass (MM) and the number of hydroxyl and aromatic rings but also on their location in the molecule, which affects their molecular bulk, flexibility and hydrophobicity, and ultimately their biological effect [42][43][44][45][46] .…”
mentioning
confidence: 99%
“…Therefore, acidizing red wine is an important step in red wine making to attain the certain levels of acidity with pleasant taste for wide consumers' acceptability. Further, tannin has been reported to promote the stability of red wine by removing metal ions and lowering the content of aldehydes materials (Picariello et al, 2016) besides its bacteriostatic action (Sekowski et al, 2017). On the other hand, glucose as source of energy or substrate material for yeast used in the required fermentation is mainly resolved into ethyl alcohol and water through glycolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the structural and functional relationship between plasma proteins and tannins. Sekowski and coworkers demonstrated that hydrolysable tannins interact very strongly with HSA, with an intensity of the interaction that depends not only on the number of hydroxyl groups, but also on the bulk, flexibility and hydrophobicity of the chemical structure [ 55 , 56 ]. Tannins with higher molecular weight bind with stronger interaction to proteins, but also tannin flexibility has to be considered: the more flexible the structure, the more rotational capacity of the molecule and easier access to protein binding pockets [ 55 ].…”
Section: Phenolic Compounds and Plasma Protein Bindingmentioning
confidence: 99%
“…Sekowski and coworkers demonstrated that hydrolysable tannins interact very strongly with HSA, with an intensity of the interaction that depends not only on the number of hydroxyl groups, but also on the bulk, flexibility and hydrophobicity of the chemical structure [ 55 , 56 ]. Tannins with higher molecular weight bind with stronger interaction to proteins, but also tannin flexibility has to be considered: the more flexible the structure, the more rotational capacity of the molecule and easier access to protein binding pockets [ 55 ]. Thus, larger and more flexible molecules are capable of changing the secondary structure of albumin through surface interactions, but the presence of valoneoyl structures limit the capacity of tannins to penetrate the hydrophobic tryptophan pocket [ 55 , 56 ].…”
Section: Phenolic Compounds and Plasma Protein Bindingmentioning
confidence: 99%